Research of Medical Intelligent Diagnosis System Based on Elasticsearch - Yun Hu, Libao Xing, Xintang Liu, Zuojian Zhou, Guokai Han, Hui Li, Chunting Wang (Forest Chemicals Review)
To address the problems that the experience of ambulance accompanying doctors is insufficient, and that hospitals have difficulty in obtaining diagnostic information of patients’ diseases before the ambulance arrives at the hospital, and thus cannot make emergency preparations in advance. A medical intelligent diagnosis system with Elasticsearch as the core, combined with Spring Boot open source technology framework, python web crawler and other technologies has been studied and implemented. Extensive tests show that the system has a high accuracy of diagnosis, up to 83%; The diagnostic results are complete, including various types of information such as clinical examinations, commonly used drugs and treatments; and the average response time for diagnosis is about 21.27ms. Consequently, the system has a certain auxiliary function for the diagnosis of emergency patients.